Exploring the Perceived Impact of the COVID-19 Pandemic Social Distancing Measures on Athlete Wellbeing: A Qualitative Study Utilising Photo-Elicitation - Woodford, Lindsay; Bussey, Lauren (Frontiers in Psychology, 2021)
Countries all over the globe have implemented mandatory social distancing measures in an attempt to suppress and control the spread of the Coronavirus disease (COVID-19). This enforced period of isolation, disruption to normal training routines and competition cancellation, could be having an adverse effect on the mental health and wellbeing of athletes. This study sought to explore the perceived impact of the COVID-19 social distancing measures on athlete wellbeing. Fourteen elite athletes who were unable to train or compete due to government imposed lockdown measures were recruited to participate in this qualitative study. Utilizing the photo elicitation method, participants were asked to take a series of photographs that represented their experiences as athletes living in lockdown. These photographs were used to guide discussions in follow up unstructured interviews. Reflexive inductive thematic analysis identified three main themes that captured athletes’ experience of social distancing measures and the implications for their wellbeing: (1) threats to wellbeing; (2) adapting routines and maintaining motivation; and (3) reflecting on participation in competitive elite sport. The initial sudden loss of sport in the athlete’s lives posed a threat to their wellbeing, but over the duration of the lockdown period the athletes developed numerous strategies to protect their wellbeing. Furthermore, their time away from sport encouraged them to reflect on their athletic identity and to make life changes that would protect their wellbeing during the rest of the lockdown period and when they returned to sport. A number of immediate practical recommendations are offered for athlete support personnel working with athletes during the crisis, these include developing self-care strategies and social networks, adapting routines, setting new goals and encouraging the pursuit of dual-careers. Future research is encouraged to investigate how practitioners can deliver effective psychological support through tele-consulting, and to consider whether their support is best focused on therapeutic counselling or mental skills training during the pandemic.